Features of Psychological Well-being Structure in Secondary School Students and Students from Different Areas of Vocational Training - Buchatskaya M. V.; Kapranova M. V. (Moscow State University of Psychology and Education, 2015)
We raise the problem of generating a differential approach to the construction of psychological programs facilitating students depending on the direction of their training. We reveal that a significant criterion for professional competence of the future professional is his psychological well-being, which structure allows to estimate the potential psychological and pedagogical assistance. The results of empirical studies of the structure of psychological well-being (with the use of C.D. Ryff Scales of Psychological Well-Being) based on the diagnostic sample of 300 people: students of universities and colleges, students enrolled in the areas of training "State and municipal management" and "Psychology". The results reveal the structural features of the psychological well-being as subjective integral index in each group of students and allow them to be regarded as a differential criterion of optimization of educational resources